F(x) = √(5x + 7)
g(x) = √(5x - 7)
(f + g)(x) = f(x) + g(x)
(f + g)(x) = √(5x + 7) + √(5x - 7)
Answer: C)
Answer:
14/3
Step-by-step explanation:
Simplify the following:
48/6 - 10/3
Hint: | Reduce 48/6 to lowest terms. Start by finding the GCD of 48 and 6.
The gcd of 48 and 6 is 6, so 48/6 = (6×8)/(6×1) = 6/6×8 = 8:
8 - 10/3
Hint: | Put the fractions in 8 - 10/3 over a common denominator.
Put 8 - 10/3 over the common denominator 3. 8 - 10/3 = (3×8)/3 - 10/3:
(3×8)/3 - 10/3
Hint: | Multiply 3 and 8 together.
3×8 = 24:
24/3 - 10/3
Hint: | Subtract the fractions over a common denominator to a single fraction.
24/3 - 10/3 = (24 - 10)/3:
(24 - 10)/3
Hint: | Subtract 10 from 24.
| 2 | 4
- | 1 | 0
| 1 | 4:
Answer: 14/3
Your answer will be x= -4y/3 + 55/3
I assume that the given equation above is 0.9(x+1.4)−2.3+0.1x=1.6 and not 0.9(x+1.4)−2.3+0.1x=1.60.9(x+1.4)−2.3+0.1x=1.6, I think there is a typo error on this. Based on equation I assumed the answer is 2.64.Thank you for posting your question here, I hope my answer helps.
Answer:
The correct way to set up the slope formula for the line that passes through points (5 , 0) and (6 , -6) is
⇒ C
Step-by-step explanation:
The formula of the slope of a line passes through points
and ![(x_{2},y_{2})](https://tex.z-dn.net/?f=%28x_%7B2%7D%2Cy_%7B2%7D%29)
is ![m=\frac{y_{2}-y_{1}}{x_{2}-x_{1}}](https://tex.z-dn.net/?f=m%3D%5Cfrac%7By_%7B2%7D-y_%7B1%7D%7D%7Bx_%7B2%7D-x_%7B1%7D%7D)
∵ The line passes through points (5 , 0) and (6 , -6)
∴
= 5 and
= 6
∴
= 0 and
= -6
Substitute these values in the formula of the slope
∵ ![m=\frac{y_{2}-y_{1}}{x_{2}-x_{1}}](https://tex.z-dn.net/?f=m%3D%5Cfrac%7By_%7B2%7D-y_%7B1%7D%7D%7Bx_%7B2%7D-x_%7B1%7D%7D)
∴ ![m=\frac{-6-0}{6-5}](https://tex.z-dn.net/?f=m%3D%5Cfrac%7B-6-0%7D%7B6-5%7D)
Let us look to the answer and find the same formula
The answer is:
The correct way to set up the slope formula for the line that passes through points (5 , 0) and (6 , -6) is ![\frac{-6-0}{6-5}](https://tex.z-dn.net/?f=%5Cfrac%7B-6-0%7D%7B6-5%7D)